The Relationship Between Self-Care Management and Medication Adherence Among Patients with Type 2 Diabetes Mellitus in the Working Area of UPTD Puskesmas III North Denpasar - Ni Putu Novi Wulandari; Ketut Lisnawati; Ni Wayan Trisnadewi (International Journal of Health Engineering and Technology, 2026)
Type 2 Diabetes Mellitus is a chronic disease that requires long-term management through the implementation of self-care management and medication adherence. Low medication adherence remains a significant problem that leads to suboptimal disease control and an increased risk of complications. This study aimed to determine the relationship between self-care management and medication adherence among patients with Type 2 Diabetes Mellitus in the working area of UPTD Puskesmas III North Denpasar. This study employed a descriptive correlational design with a cross-sectional approach. A total of 104 respondents were selected using purposive sampling. Data were collected using the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire and the Morisky Medication Adherence Scale-8 (MMAS-8). Data analysis was conducted using the Spearman Rank correlation test. The results showed that most respondents had a moderate level of self-care management (67.3%) and a low level of medication adherence (57.7%). Statistical analysis revealed a p-value of 0.001 with a correlation coefficient of r = 0.554, indicating a positive and significant relationship with moderate strength. These findings indicate that improved self-care management plays an important role in enhancing medication adherence through increased patient understanding and responsibility for treatment. This study highlights the importance of self-care management education and continuous support in the management of Type 2 Diabetes Mellitus.